Bioavailability of Gentamicin and Vancomycin Released from an Antibiotic Containing Bone Cement in Patients Undergoing a Septic One-Stage Total Hip Arthroplasty (THA) Revision: A Monocentric Open Clinical Trial. Issue 1 (January 2016) - Kendoff, Daniel O.; Gehrke, Thorsten; Stangenberg, Peter; Frommelt, Lars; Bösebeck, Hans
Background: The purpose of this clinical investigation was to evaluate the systemic bioavailability of antibiotics from bone cement after implantation. This was done by determining the concentrations of gentamicin and vancomycin in plasma and urine of patients receiving a novel bone cement during one-stage revision in periprosthetic hip infections. The local concentrations of both antibiotic agents in wound exudate as well as the efficacy and tolerability were assessed as a secondary objective. Methods: In a prospective open clinical trial, 20 patients (mean age 62.5 years) with an implanted hip prosthesis requiring revision due to periprosthetic infection were treated with this antibiotic loaded bone cement (ALBC) between 2009 and 2011. The concentrations of gentamicin and vancomycin in plasma, urine and wound exudate were determined with quantitative liquid chromatography analysis (LC-MS-MS). Results: The mean postoperative maximum gentamicin plasma concentration at 5.85 hours was 209.65 ng/mL. For vancomycin, a mean postoperative maximum plasma concentration of 134.64 ng/mL was determined at 20.03 hours. Small amounts of both antibiotics were excreted via the urine within the first 10 days after surgery. No reinfection was observed at the end of the hospital stay or during the follow-up period up to 7 months post surgery. Conclusions: Slow absorption of both antibiotics after release from the cement resulted in plasma concentrations well below toxic levels and did not result in a critical systemic concentration potientially inducing bacterial resistance. The treatment with this novel bone cement was assessed as efficacious and was very well tolerated by all patients.